PCR Positivity of Gerbils and Their Ectoparasites for Leishmania Spp. in a Hyperendemic Focus of Zoonotic Cutaneous Leishmaniasis in Central Iran - Sahar Azarmi; Alireza Zahraei-Ramazani; Mehdi Mohebali; Yavar Rassi; Amir Ahmad Akhavan; Amrollah Azarm; Omid Dehghan; Samira Elikaee; Rahimeh Abdoli; Mohsen Mahmoudi (Tehran University of Medical Sciences, 2023)
Background: Various arthropods, including Rhipicephalus sanguineus and Ctenocephalides felis felis have been suggested as secondary vectors of Leishmania spp. many years ago. This study was conducted to determine zoonotic cutaneous leishmaniasis (ZCL) PCR positivity of reservoir hosts and their ectoparasites for Leishmania spp. in Segzi plain in Esfahan Province from October 2016 to October 2017. Methods: Microscopic examination and nested PCR were used to detect and identify Leishmania spp. isolated from rodents' ear and ectoparasites, and then, the results were confirmed by two methods, PCR-restriction fragment length polymorphism and sequencing. Results: Totally, 93 rodents (92 Rhombomys opimus and one Nesokia indica) and nine different species of ectoparasites (n=527) including fleas, mites, and ticks were collected during different seasons in the study area. Fourteen R. opimus were positive for Leishmania spp. by microscopic examination while one N. indica and 77 R. opimus were positive by nested PCR. The infection rate of rodents with Leishmania major and L. turanica was 39.79% (n=37) and 15.05% (n=14), respectively. Mixed natural infections with L. major and L. turanica were seen in rodents. Moreover, 72.22% of fleas (39/54), 75.0% of mites (5/8), and 100% of tick nymph (1/1) were PCR positive for Leishmania parasites. Conclusions: The highest rate of infection with L. major and L. turanica in R. opimus populations was observed in summer and spring, respectively. It is suggested that the role of L. turanica and the probable role of ectoparasites in the epidemiology of disease should be investigated. Xenodiagnostic testing is recommended for future testing.